Validity of Optical Practicum KIT Equipped with Guided Inquiry-Based Worksheet for Madrasah Aliyah Students - Isnaniah, Nur; Rahmawati, Irma (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2024)
The background of this research is the lack of supporting facilities for physics practicum activities, such as laboratories and teaching aids, so skills competence in optical material is not carried out. This study aimed to determine the validity of the Optical Practicum KIT with the validity of the Guided Inquiry-based worksheets. This study uses the Research and Development (R&D) method with the ADDIE model (Analyze, Design, Development, Implementation, and Evaluate). The data in this study are product validity obtained from 3 expert validators. The research results data were then analyzed using quantitative descriptive and qualitative descriptive analysis techniques. The results showed that the validity of the Optical Practicum KIT was stated to be very valid by the validator with a value of 84,83%, and the validity of the Guided Inquiry-based worksheet was also stated to be very valid with a value of 89,56%, so it was suitable for use as a physics learning medium. Hopefully, this research can be further refined in terms of construction and adding components such as microcontroller sensors, as well as implementing or testing products with experimental research.